1963
DOI: 10.1029/jz068i004p01145
|View full text |Cite
|
Sign up to set email alerts
|

Depth to magnetic ‘basement’ in west Antarctica

Abstract: The results of aero.magnetic flights in a portion of West Antarctica are presented and discussed. On the basis of short-wavelength magnetic anomalies, Byrd basin is shown to represent a geologic boundary. Depth determinations to anomaly sources show the absence of a thick sedimentary rock section within and to the north and west of Byrd basin and suggest a probable thickening of sedimentary rock to the east and south. The aeromagnetic method of determining depth to magnetic 'basement' gives a limit of possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…These amplitudes are very high considering that the shallowest possible sources lie at a minimum of 1.5 km below the survey aircraft; the vast majority are >3 km. The sources of most of the short-wavelength anomalies dominating the magnetic field are essentially at the base of the ice and are interpreted to be caused mostly by late Cenozoic subvolcanic intrusions and some thick flows which we term ''volcanic centers'' as discussed by Behrendt and Wold (1963), Behrendt, 1964, Behrendt et al (1991a,b, 1994, 2002a and Jankowski et al (1983). Jonsson et al (1991) showed and discussed the magnetic anomaly map of Iceland, which is entirely a volcanic terrane; the similarity of this map and other aeromagnetic surveys over volcanic terranes to Fig.…”
Section: Aeromagnetic and Radar Ice Sounding Surveymentioning
confidence: 97%
See 2 more Smart Citations
“…These amplitudes are very high considering that the shallowest possible sources lie at a minimum of 1.5 km below the survey aircraft; the vast majority are >3 km. The sources of most of the short-wavelength anomalies dominating the magnetic field are essentially at the base of the ice and are interpreted to be caused mostly by late Cenozoic subvolcanic intrusions and some thick flows which we term ''volcanic centers'' as discussed by Behrendt and Wold (1963), Behrendt, 1964, Behrendt et al (1991a,b, 1994, 2002a and Jankowski et al (1983). Jonsson et al (1991) showed and discussed the magnetic anomaly map of Iceland, which is entirely a volcanic terrane; the similarity of this map and other aeromagnetic surveys over volcanic terranes to Fig.…”
Section: Aeromagnetic and Radar Ice Sounding Surveymentioning
confidence: 97%
“…1) throughout the West Antarctic rift system as evidence of subglacial eruptions. High-amplitude magnetic anomalies have been long known to mark volcanoes and exposures of volcanic rocks in the rift and provided initial evidence of extensive deposits of inferred volcanic rocks beneath the WAIS (e.g., Behrendt and Wold, 1963;Behrendt 1964). The extent of submarine and subglacial late Cenozoic volcanism is inferred, from geophysical data, to be much larger than the mapped volcanic exposures (Fig.…”
Section: Glacial Removal Of Unconsolidated Volcanic Edifices Erupted mentioning
confidence: 98%
See 1 more Smart Citation
“…The basement rocks and overlying sediments were intruded by a series of diabase sills, the the rocks are described by location, magnetite An estimate of the lower limit of suscepticontent, and susceptibility estimated using the bility of the rock causing the Mount Erebus formula k • 0.3P (emu), where k is bulk sus-anomaly can be obtained from the data along ceptibility, P is percentage of magnetite, and line A-A'. The anomaly was assumed to be from geologic effects; therefore, in the past [Behrendt and Wold, 1963;Behrendt, 1964;Robinson, 1962], geological interpretation has been restricted to anomalies greater than 100 to 200 7 in amplitude. Profiles A and B were recorded on the ice plateau surface, generally more than 2 km above the rock surface.…”
Section: The Grid Survey Of Ross Island Was Made Inmentioning
confidence: 99%
“…70° W. may actually be farther to the north and that the mountains( ?) in this area m ay be the sam e as those studied b y the Anta rctic Peninsula traverse (Behrendt, 1963) in the v icinity of lat. 75° S., long.…”
Section: Introductionmentioning
confidence: 95%